Assessing 15 Proposals for Promoting Innovation and Access to Medicines Globally - Steven J. Hoffman; Karen So (Ubiquity Press, 2015)
Background There is widespread recognition that the existing global systems for innovation and access to medicines need reform. Billions of people do not have access to the medicines they need, and market failures prevent new drugs from being developed for diseases that primarily affect the global poor. The World Health Organization's Consultative Expert Working Group on Research and Development: Financing and Coordination (CEWG) analyzed numerous proposals for reform. The aim of this article is to build on these previous inquiries. Methods We conducted a structured analysis that grouped proposals into five broad opportunities for global policy reform to help researchers and decision makers to meaningfully evaluate each proposal in comparison with similar proposals. Proposals were also analyzed along three important dimensions-potential health impact, financial implications, and political feasibility-further facilitating the comparison and application of this information. Findings Upon analysis, no one solution was deemed a panacea, as many (often competing) considerations need to be taken into account. However, some proposals, particularly product development partnership and prizes, appeared more promising and feasible at this time and deserve further attention. Conclusion More research is needed into the effectiveness of these mechanisms and their transferability across jurisdictions.